Simplified Linear Configuration Model of 3X3 Single Mode Fiber Coupler using Matrix Transfer - Saktioto Saktioto; Dedi Irawan; Defrianto Defrianto (Universitas Ahmad Dahlan, 2015)
Experimental design and operation of a directional fiber coupler having identical-output ratio is successfully fabricated. The coupling region is imposed by fusion temperature 800-1350 0C injecting the Hydrogen gas at 1Atm. Concurrently the coupled-mode theory is used to model power transfer between the waveguides by using transfer matrix method. By 1mW source input power to one of three input ports, it shows that power propagation among three coupled fibers is normalized; the optical fiber are nearly identical and a similar separation between them. The matrix configuration of 3X3 is also used to calculate the polarization effect of directional fiber coupler. It is found that the incident power polarized with various angle causes power output at both three output ports decrease exponentially. This 3X3 directional fiber coupler design is a significant passive component for various functions power splitter and routers.